2018
DOI: 10.1111/bph.14092
|View full text |Cite
|
Sign up to set email alerts
|

Sophocarpine attenuates wear particle‐induced implant loosening by inhibiting osteoclastogenesis and bone resorptionviasuppression of the NF‐κB signalling pathway in a rat model

Abstract: SPC can prevent implant loosening through inhibiting osteoclast formation and bone resorption. Thus, SPC might be a novel therapeutic agent to prevent prosthesis loosening and for osteolytic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 68 publications
(90 reference statements)
0
31
0
Order By: Relevance
“…Subsequently, mature osteoclasts undergo polarization and structural changes to produce a tight sealing zone. Secretion of acids and proteolytic enzymes into this sealing zone results in the dissolution and degradation of the underlying bone …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, mature osteoclasts undergo polarization and structural changes to produce a tight sealing zone. Secretion of acids and proteolytic enzymes into this sealing zone results in the dissolution and degradation of the underlying bone …”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have focused on natural compounds because of their pharmacological activity against human diseases. Over several years, our group has screened natural compounds for treating osteoclast‐related diseases . Stachydrine (STA), a bioactive constituent extracted from a medicinal herb Leonurus heterophyllus Sweet, has extensive pharmacological properties, including antioxidant, anti‐inflammatory, anticancer and cardioprotective properties .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, NF-κB activation contributes to osteoclast differentiation and maturation vis the binding of RANKL and osteoclastassociated RANK [14]. A number of researchers have reported that repressing NF-κB signaling pathway activation could attenuate wear debris-induced osteolysis [15][16][17]. Our previous study has proved that the PI3K/Akt pathway plays a positive role in the regulation of activating macrophages by wear particles.…”
Section: Introductionmentioning
confidence: 99%